PENYELESAIAN SENGKETA HIBAH MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Apri Rotin Djusfi; Jumadi Winata (Prodi Ilmu Hukum, Universitas Teuku Umar, 2019)
Article 1666 of the Civil Code provisions regarding grants are regulated in the Civil Code Chapter X Book III concerning Engagement affirms that a Defend is an agreement, whereby an donor submits an item free of charge, without being able to withdraw it, for the benefit of someone who receives the goods and must include all heirs. However, there are still many grants that do not include all heirs in the granting of these grants, which makes other legitimate heirs do not accept the existence of these grants and they want to complete them. To obtain data in this thesis writing, literature research and field research are conducted. Library research to obtain secondary data by studying books, legislation. Compliance in the Civil Code is only an obligator, meaning that it has not transferred ownership rights, because the ownership rights have just moved by levering or juridical submission. It is said that granting is not a sale and purchase and exchange but one of the titles for the transfer of ownership. Keywords: grant, civil code, private law